Optimalisasi Peran Keluarga melalui Peningkatan Pengetahuan dalam Menjaga Kesehatan Mental pada Remaja - Puji Lestari; Liyanovitasari Liyanovitasari; Mona Saparwati; Heri Prabowo (Lembaga Pengembangan Kinerja Dosen, 2025)
In addition to physical health, mental health in adolescents really needs attention. Mentally healthy individuals can function normally in carrying out their lives, especially when adjusting to face problems that will be encountered throughout a person's life. The role of parents in the family is very influential, especially on the mental development of children. The service activities carried out in Gogik Village are providing education to families about adolescent mental health and how to maintain adolescent mental health. Based on an initial survey conducted to adolescent families in Gogik Village who were present, it was found that more than 87.5% of families did not know about how to maintain mental health in adolescents. Before being given increased knowledge with health education, out of 32 participants, 28 (87.5%) had less knowledge in maintaining mental health in adolescents. After being given increased knowledge with Health Education, it was known that as many as 32 participants (100%) had good knowledge in maintaining mental health in adolescents